Plasma Concentration of Irisin and Brain-Derived-Neurotrophic Factor and Their Association With the Level of Erythrocyte Adenine Nucleotides in Response to Long-Term Endurance Training at Rest and After a Single Bout of Exercise - Rodziewicz, Ewa; Król-Zielińska, Magdalena; Zieliński, Jacek; Kusy, Krzysztof; Ziemann, Ewa (Frontiers in Physiology, 2020)
The study aimed to assess the effect of a single bout of incremental exercise on irisin and BNDF plasma concentrations as related to erythrocyte purine nucleotides concentration at rest and after exercise. Master endurance master athletes (training experience 38±6years) and a group of untrained participants completed a single bout of progressive incremental exercise test until exhaustion. The dual-energy x-ray absorptiometry and blood collection were performed. Blood was taken twice at rest and 10 minutes after exercise. Concentrations of ATP, ADP and AMP were assessed in the erythrocytes. Hypoxanthine and uric acid were determined in plasma using the high-performance liquid chromatography. Plasma concentrations of irisin and BDNF were assessed through the immunoenzymatic method. The ATP level, ATP/ADP ratio and AEC value were significantly higher in the athletes’ group. A significantly higher concentration of BDNF was noted also in the trained group that correlated with the erythrocyte’s energy status at rest. The single session of exercise induced a significant increase in ATP erythrocyte levels in both groups. Both exerkines significantly correlated at rest with red blood cell adenine nucleotides and degradation products (BDNF positively and irisin negatively). The blood concentration of BDNF and irisin, in response to exercise, was not significantly different between groups. Obtained data revealed a higher erythrocyte energy status and lower purine degradation products concentration in master athletes. Also resting plasma exerkines differed substantially between groups. In conclusion, long-term training resulted in exercise adaptation reflected by a higher erythrocyte energy status, lower purine degradation products concentration and modified concentration of exerkines (higher BDNF and lower irisin blood concentrations). Therefore, we consider the training adaptations induced by master athletes to be beneficial and significant. The moderate level of physical activity in the untrained group, even if it is sufficient in in terms of general health, did not cause any discernible changes.